Penerapan Model Pembelajaran Problem Based Learning dalam Pembelajaran IPAS tentang Aku dan Kebutuhanku untuk Meningkatkan Hasil Belajar Siswa di Kelas IV SD Kristen Anugerah Haukoto - Epivanius Trihendo Anunu; Antonius Suban Hali; Adam Bol Nufu Benu (ARZUSIN, 2025)
The low learning outcomes of fourth-grade students at SD Kristen Anugerah Haukoto on the topic Aku dan Kebutuhanku, which failed to meet the Minimum Mastery Criterion (Kriteria Ketuntasan Minimal, KKM) of 75, serve as the background for this study. The primary objective is to improve student learning outcomes in IPAS (Science, Environment, Technology, and Society) through the implementation of the Problem-Based Learning (PBL) model. This research employed a Classroom Action Research (CAR) method conducted over two cycles, each consisting of planning, implementation, observation, and reflection stages. Data collection techniques included observations of teacher and student activities, as well as learning outcome tests. The study involved 23 students, comprising 8 boys and 15 girls. Results showed a significant increase in learning mastery, from 8.69% in the pre-cycle phase to 30.43% in the first cycle, and reaching 86.95% in the second cycle. These findings affirm that the Problem-Based Learning model is effective in enhancing student learning outcomes on the topic Aku dan Kebutuhanku. The study underscores the importance of teachers mastering instructional models to guide students in solving problems actively and purposefully.